Perlindungan Hukum Pemegang Hak Waralaba di Indonesia - Ginting, Jamin; Sari, Vincensia Esti Purnama (Pelita Harapan University, 2006)
Franchise Agreement is regarded as legal guide to certify the rights and obligations of franchisor as well as franchisee. Since the issuance of rights in a franchise is set in a certain agreement/contract, both parties (franchisor & franchisee) demand their rights to be protected by the agreement. The objective of the protection is to secure the risk that might arise if one party breaches the agreement. Â Â The research indicated that some clauses in the Franchisee Agreement are not protecting the franchisors need i.e: a. The clause relating the raw materials should come from the franchisor, b. The law applicable should be the law of the franchisor, c. The franchisor in entitled to all property rights and innovation made by franchisee, and other clauses which effect the franchisee, especially local franchise in Indonesian. Recently the law relating with franchise in Indonesian is only regulated in Government Regulation Number 16 Year J997 concerning franchise, and Minister of Trade and Industry Regulation Number 259/MPP/Kep/7/1997. In this case both regulation are not much of a help in protecting the Franchise Agreement in Indonesia since those regulation are not sufficient in providing direction and guidance to issue the Government Regulation.